Post Cesarean Surgical Site Infection With Mycobacterium Abscessus Sp. Massiliense - Ruchi Nagpal; Hari Pankaj Vanam; Harshi Dhingra; Ravali R Banswada (Tehran University of Medical Sciences, 2022)
Objective: Surgical site infections (SSIs) owing to nontuberculous Mycobacteria (NTM) have emerged as an important cause of hospital-acquired SSI leading to great morbidity and mortality. Among NTM, Mycobacterium abscessus is reported in these sites. Epidemiology and transmission of M. abscessus in humans is noticing crux changes. Case report: We hereby describe a case of SSI after lower segment cesarean section (LSCS), presenting as a skin and soft tissue infection (SSTI) owing to a NTM. Conclusion: Clinicians should be aware of the possibility of infections caused by M. abscessus in patients who develop SSIs, particularly if they do not respond to conventional first-line antimicrobial therapy.